The Effect of Thinking-Based STEM Learning on Students' Critical Thinking Ability - Meza Mardita; Jesi Alexander Alim; Neni Hermita; Tommy Tanu Wijaya (Universitas Negeri Makassar, 2022)
The purpose of this study was to examine the differences in the improvement of students' critical thinking skills between students who received treatment using the MIKiR-based STEM learning approach and students who only used conventional learning at the 191 Pekanbaru State Elementary School in science learning material energy sources. The research method used is a quantitative research method that uses an experimental design using 2 classes as the control group and the experimental group. Each class will be given a pre-test before being given treatment and a post-test given treatment. The results showed that there was a significant effect of the application of MIKiR-based STEM learning on the critical thinking skills of fourth grade students at SDN 191 Pekanbaru in science learning where the significance value was 0.000 <0.05. Therefore, it can be said that there is a significant effect on the application of MIKiR-based STEM learning on students' critical thinking skills on energy source materials.